Stachytarpheta urticifolia Sims, a New Snakeweed Record for the Flora of Manipur, India - Nanda Devi, Y.; Singh, P. K. (Indian Forester, 2005)
Stachytarpheta urticifolia Sims a rare snakeweed and not reported earlier from Manipur has been recently collected. In this paper, the identity of S. cayennensis (Rich.) Vahl for the flora of Manipur State which have identified as S. jamaicensis (Linn.) Vahl by various authors, has been clarified. Detailed morphological descriptions and line drawings of Stachytarpheta urticifolia Sims have been presented.